2022
DOI: 10.1021/acsenergylett.2c00364
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Transitions and Energy Transfer Processes in Sb-Based Zero-Dimensional Metal Halide Nanocrystals Doped with Manganese

Abstract: Antimony-based 0-dimensional metal halides (0D-MHs) are attracting attention owing to their bright Stokes-shifted luminescence due to self-trapped excitons (STEs). One unexplored motif to expand their functionalities is to dope them with optically and/or magnetically active dopants that participate in energy-transfer schemes involving STEs. We investigated the photophysical and magnetic properties of Rb7Sb3Cl16 nanocrystals doped with Mn2+ ions, which introduce strong magnetism and activate their characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 79 publications
3
27
0
Order By: Relevance
“…These are typical spectroscopic signatures of the activation of inter-Mn exciton migration promoting PL quenching in defect sites, in agreement with previous reports. 57 , 71 , 72 EPR spectra of Cu-alloyed Cs 3 ZnCl 5 NCs with increasing Mn content corroborate this picture, showing the transition from the typical signature of nearly isolated Mn 2+ ions (i.e., the six evenly spaced resonances because of the 55 Mn hyperfine transitions) in lightly alloyed particles (4.5%Mn–4.6%Cu sample) into coupled Mn 2+ centers with increasing alloying level resulting from the magnetic dipolar broadening between Mn spin centers ( Figure 2 f). The relatively large isotropic hyperfine splitting A ∼230 MHz obtained from the EPR spectrum for the sample 4.5%Mn–4.6%Cu sample suggests that paramagnetic Mn ions are preferentially located at the surface of the NCs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These are typical spectroscopic signatures of the activation of inter-Mn exciton migration promoting PL quenching in defect sites, in agreement with previous reports. 57 , 71 , 72 EPR spectra of Cu-alloyed Cs 3 ZnCl 5 NCs with increasing Mn content corroborate this picture, showing the transition from the typical signature of nearly isolated Mn 2+ ions (i.e., the six evenly spaced resonances because of the 55 Mn hyperfine transitions) in lightly alloyed particles (4.5%Mn–4.6%Cu sample) into coupled Mn 2+ centers with increasing alloying level resulting from the magnetic dipolar broadening between Mn spin centers ( Figure 2 f). The relatively large isotropic hyperfine splitting A ∼230 MHz obtained from the EPR spectrum for the sample 4.5%Mn–4.6%Cu sample suggests that paramagnetic Mn ions are preferentially located at the surface of the NCs.…”
Section: Resultsmentioning
confidence: 99%
“…The PLQY values of these Cu, Mn coalloyed NCs was essentially constant (around 3%) apart for the sample featuring the highest Mn content (PLQY < 1%). The analysis of the Mn PL dynamics and the EPR spectra indicated that this QY drop stems from inter-Mn exciton migration, which increases the likelihood of trapping in defect sites, in agreement with previous studies on Mn-doped systems …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…23,24 For instance, when the nanocrystals reach a sufficiently small size, the original continuous energy level structure near the Fermi level becomes an atom-like discontinuous energy level structure. 25 The electrons in the valence band will absorb energy when excited by external light and become unstable and jump between these discontinuous energy levels to the high-energy conduction band, thus generating carriers. Therefore, the effect of the unique size of nanocrystals can increase the carrier separation efficiency.…”
Section: Basic Propertiesmentioning
confidence: 99%